Zakażenie Salmonella enteritidis imitujące neuroinfekcję u czternastoletniego pacjenta - opis przypadku - Szczepaniak, Kinga; Szewczyk, Martyna; Pokorska-Śpiewak, Maria (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Salmonella bacilli are the most common cause of bacterial foodborne diseases in Poland. Due to heterogeneous clinical course, they may cause an essential problem during differential diagnosis. In this paper we aimed to present a case report of a 14-year-old patient infected with Salmonella enteritidis, in whom the disease initially imitated the symptoms of bacterial meningitis. We described the difńculties within the diagnostic process and the chosen treatment. This case report demonstrates that Salmonella infection, due to its heterogeneous clinical course, may cause an important diagnostic and therapeutic problem.